Comparison Between Guided and Non-Guided Homework as a Tool for Learning Electric Circuit Theory - Rafael Diez; Arturo Fajardo; Jairo A. Hurtado (Education Sciences)
The present work highlights the differences between two simultaneous groups taking the electric circuit theory course. Both groups were given the same non-mandatory homework prior to the evaluation; however, the instructions provided to the groups differed. Historically, this homework has been assigned without any guidelines, and instructors have not been aware of whether students completed the task. In this study, specific instructions were developed to simulate the same stressful conditions regarding time constraints for finding the correct answer that students face during an exam. The results indicate that the group of students who received categorized exercises along with a structured schedule performed better than the non-guided group (2.8/5 versus 2.3/5 on average). The study also reveals that a significant portion of students engaged with this optional activity during the initial weeks (45%), but this engagement decreased substantially over time (to 5%), showing a correlation between evaluation results and commitment to the exercises. Sharing these findings with students may help improve performance in a course that historically has had a pass rate below 50%.